Coherent flow noise beneath a flat plate in a water tunnel experiment. (31st March 2015) - Abshagen, J.; Schäfer, I.; Will, Ch.; Pfister, G.
Abstract: Results from a combined experimental and numerical study on the properties of flow noise on the reverse side of a flat plate excited by a turbulent boundary layer flow are reported. Particular focus is given to the coherence between wall pressure fluctuations, plate vibrations, and interior flow noise. The plate was immersed in water and laterally attached to a streamlined model inside the HYKAT cavitation tunnel at HSVA Hamburg (Germany). The flow velocity in the tunnel was U =7 m/s. Simultaneous measurements of wall pressure fluctuations, structural vibrations, and interior flow noise as well as a numerical response and eigenvalue analysis provide evidence that evanescent plate modes excited by wall pressure fluctuations play a crucial role in flow noise generation. Flow noise in the (quiescent) water inside of the model is found to have large coherence lengths and pronounced amplitudes for distinct frequencies below f ≈ 300 Hz .